Private benefits and minority shareholder expropriation: Empirical evidence from IPOs of German family-owned firms - Olaf Ehrhardt; Eric Nowak (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
Our study examines the existence and the nature of private benefits of control in Germany. We do this by analyzing initial public offerings of founding-family owned firms and tracking their fate up to ten years following the IPO. Our sample includes a uniquely rich data set of 105 IPOs of family-owned firms floated from 1970 to 1991 on German stock exchanges. We find that, first, even ten years after the IPO, family owners, in the cross section, continue to exercise considerable control. Second, we show that there exist substantial private benefits of control in these firms and - to our understanding for the first time - we empirically measure what the nature of these private benefits really is. We also show that the separation of cash flow rights and voting rights via the issuance of dual-class shares is used to create controlling shareholder structures in order to preserve these private benefits. Third, we find a puzzling and significant underperformance of dual-class share IPOs, which can be explained by ex ante unanticipated expropriation of minority shareholders due to poor investor protection in Germany.
urn:nbn:de:hebis:30-9871
Keywords: G14; G32; G15; 330; Private benefits; Initial Public Offerings; Dual-class shares; Control transfers; Ownership structures; Investor protection